THE EFFECTIVENESS OF IMPLEMENTING A DIFFERENTIATED INSTRUCTION TEACHING MODULE THROUGH A PROBLEM-BASED LEARNING MODEL IN IMPROVING STUDENTS PROBLEM-SOLVING SKILLS - Dwi Rahma Khauliyani; Ida Dwijayanti; Sugiyanti Sugiyanti (FKIP Universitas Muhammadiyah Tangerang, 2026)
This study aims to examine the effectiveness of a differentiated learning module based on Problem-Based Learning (PBL) in improving students’ mathematical problem-solving skills on the topic of Systems of Two-Variable Linear Equations (SPLDV). Using a quantitative approach with a pretest–posttest control group design, the research involved an experimental class that received instruction using the differentiated PBL-based module and a control class that followed conventional learning. Primary data were obtained from pretest and posttest scores, while secondary data consisted of expert validations and student response questionnaires. The results showed that the module met the feasibility criteria based on evaluations from material and media experts. Statistical analysis indicated that the experimental class demonstrated significantly higher improvement than the control class. The independent t-test confirmed a significant difference in posttest scores, the classical mastery level exceeded the 75% threshold, and the N-Gain score fell into the high category. These findings suggest that the differentiated PBL-based learning module is effective and suitable for enhancing students’ mathematical problem-solving abilities